Unanticipated Admission Following Outpatient Laparoscopic Cholecystectomy: Identifying Opportunities for Improvement. Issue 7 (July 2021) - Beck, Anna C.; Goffredo, Paolo; Gao, Xiang; McGonagill, Patrick W.; Weigel, Ronald J.; Hassan, Imran
Background: Unanticipated admissions are a burden to the health care system. Over 400 000 outpatient laparoscopic cholecystectomies (LCs) are performed annually in the United States. The aim of this study is to identify causes of unanticipated admissions and modifiable risk factors. Methods: Patients undergoing elective outpatient LCs were identified from the 2013-2015 American College of Surgeons National Surgical Quality Improvement Program database. Results: A total of 69 376 patients underwent outpatient LC or LC+ intraoperative cholangiogram (IOC); 2027 (2.9%) were admitted after a median of 5 days (interquartile range 3-8). Admission rates varied by preoperative indications: pancreatitis (4.9%), gallstones with obstruction (3.9%), cholecystitis (3.0%), and gallstones without obstruction (2.6%) ( P = .003). The most frequent causes were infection, retained stones, and other GI complications. Patients admitted for infection or cardiopulmonary complications were older with higher American Society of Anesthesiologists (ASA) ( P < .01), while patients with pain and retained stones were younger with lower ASA ( P < .01). Patients who underwent LC+IOC had a lower admission rate due to retained stones (.17% vs. .31% LC, P = .006). Conclusions: Unanticipated admissions following outpatient LC occur infrequently for diverse reasons usually within the first week after surgery. Associated factors are patient and disease related and not at all modifiable. In selected patients, increased IOC use may decrease admissions from retained stones.